2020
DOI: 10.7554/elife.57313
|View full text |Cite
|
Sign up to set email alerts
|

Different theta frameworks coexist in the rat hippocampus and are coordinated during memory-guided and novelty tasks

Abstract: Hippocampal firing is organized in theta sequences controlled by internal memory processes and by external sensory cues, but how these computations are coordinated is not fully understood. Although theta activity is commonly studied as a unique coherent oscillation, it is the result of complex interactions between different rhythm generators. Here, by separating hippocampal theta activity in three different current generators, we found epochs with variable theta frequency and phase coupling, suggesting flexibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 131 publications
3
70
0
1
Order By: Relevance
“…Subsequent experimental research using optogenetics methods showed our correctness. When the PV basket neurons were stimulated in the CA3 field, the theta rhythm power in the CA1 field decreased (López-Madrona et al, 2020). Our prediction about the role of the perforant path in theta rhythm generation, made in our previous work (Mysin et al, 2019), was also confirmed.…”
Section: Theta Rhythm Modelsupporting
confidence: 82%
See 1 more Smart Citation
“…Subsequent experimental research using optogenetics methods showed our correctness. When the PV basket neurons were stimulated in the CA3 field, the theta rhythm power in the CA1 field decreased (López-Madrona et al, 2020). Our prediction about the role of the perforant path in theta rhythm generation, made in our previous work (Mysin et al, 2019), was also confirmed.…”
Section: Theta Rhythm Modelsupporting
confidence: 82%
“…Our prediction about the role of the perforant path in theta rhythm generation, made in our previous work (Mysin et al, 2019), was also confirmed. The perforant path input does not play a role in theta rhythm generation, as confirmed by experiments with signal suppression from the entorhinal cortex (López-Madrona et al, 2020). Although the results (López-Madrona et al, 2020) directly contradict the results of previous studies (Middleton & McHugh, 2016).…”
Section: Theta Rhythm Modelmentioning
confidence: 56%
“…Note phase locking between both rhythms (θ-γ coupling) and the amplitude modulation of the intracellular γ; modified from Penttonen et al (1998). Jutras et al, 2009;López-Madrona et al, 2020). These authors suggest that successful memory performance requires coupling of γ rhythms to particular phases of the hippocampal θ (termed θ-γ coupling).…”
Section: θ-γ Coupling During Memory Task Performancementioning
confidence: 99%
“…During these active states, γ oscillations are prominent and also participate in memory formation (Buzsaki and Draguhn, 2004 ). γ oscillations are prominent in the entorhinal–hippocampal network during a variety of memory tasks in different species (Montgomery and Buzsáki, 2007 ; Sederberg et al, 2007 ; Jutras et al, 2009 ; López-Madrona et al, 2020 ). These authors suggest that successful memory performance requires coupling of γ rhythms to particular phases of the hippocampal θ (termed θ–γ coupling).…”
Section: Interaction Of Theta With Gamma Rhythmsmentioning
confidence: 99%
“…This interpretation is consonant with shifts in hippocampal states from pronounced theta oscillations during novel exploration, to theta-free epochs marked with sharp-wave ripple events (35) thought to support replay of prior experience (36). Eye-movement tracking therefore provided a marker of memory processing with the requisite temporal precision to resolve the behavioral ramifications of dynamic changes in hippocampal activity reflecting encoding versus retrieval that occur rapidly over a brief interval (34, 37), even during a single episode during which learning occurs for a novel stimulus.…”
mentioning
confidence: 99%